Sri Lanka : Achieving Pro-Poor Universal Health Coverage without Health Financing Reforms - Smith, Owen (World Bank, Washington, DC, 2018)
Sri Lanka’s health system has a long track record of strong performance. This case study describes the main features and achievements of Sri Lanka’s high-performing health system, to distill lessons for the rest of the world. UNICO case studies focus on a particular health coverage program. In Sri Lanka, the selected health coverage program is the government’s national health service (NHS) that was established in the 1930s and has remained broadly the same since then. Thus, the entire government health system is taken as the health coverage program, without narrowing the focus to a specific program. The relationship between the government system and the private health sector in Sri Lanka is explored in the case study. Looking forward, the pending agenda related to addressing the health needs of an aging population is also discussed.